ChemInform Abstract: La3Cu4P4O2 and La5Cu4P4O4Cl2: Synthesis, Structure and 31P Solid State NMR Spectroscopy. Issue 18 (April 2016) - Bartsch, Timo; Benndorf, Christopher; Eckert, Hellmut; Eul, Matthias; Poettgen, Rainer
Abstract: Polycrystalline La3 Cu4 P4 O2 (I) and La5 Cu4 P4 O4 Cl2 (II) are prepared by solid state reaction of stoichiometric amounts of La, Cu2 O, red P, and LaCl3 (evacuated silica tubes, 1.